Letter : Spanish seamen - Reed, George
025a-0101-001 Telegraphic Address: "SEAROVING, LAMB, LONDON" Telephone No: WATerloo 5906 (five lines) National Union of Seamen REGISTERED TRADE UNION NO 1493 APPROVED SOCIETY CERTIFICATE NO 128 Affiliated to the Labour Party, International Transportworkers Federation, Trades Union Congress. National Maritime Board (SAILORS, FIREMEN AND CATERING PANELS) EXECUTIVE OFFICERS: General Secretary: W.R. Spence C.B.E. Asst. General Secretary: G. Reed General Treasurer: J.B Wilson Registered Offices: ST GEORGES HALL, WESTMINSTER BRIDGE ROAD, LONDON S.E.1. Please quote in reply Yor Ref: HVT/EK/1108 Our Ref: GR/MLA. ALL COMMUNICATIONS MUST BE ADDRESSED TO THE GENERAL SECRETARY Mr. H.V. Tewson, May 8th 1939 Trades Union Congress Transport House, Smith Square, LONDON, S.W.1. Dear Mr. Tewson, SPANISH SEAMEN. - Newcastle subfolder Thanks for your letter of the 6th instant. I note what you say, and I am obliged also for the copy of circular sent to the Trades Councils in respect of the above. I shall advise our local secretaries that the payment and administration in respect of Spanish refugee seamen will be carried out by the local Trades Councils in the various ports where these men are living, and I feel sure that where possible the local secretaries of our Union will give advice to the local Trades Council Secretaries in regard to the matters indicated above. We have not received our cheque for the account rendered to you which amounted to £614.3.9. I would be glad if you could let us have a remittance for the amount due, as I have a Finance and General Purposes Committee shortly and I want to get these accounts squared up before they meet. Yours faithfully, Geo. Reed Assistant General Secretary. 292/946/25a/101